Comparative Genomic Analysis of Lactobacillus plantarum: An Overview - Eliane Evanovich; Patricia Jeanne de Souza Mendonça Mattos; João Farias Guerreiro (International Journal of Genomics)
Background. Lactobacillus plantarum is widely used in the manufacture of dairy products, fermented foods, and bacteriocins. The genomes of the strains contain multiple genes which may have been acquired by horizontal gene transfer. Many of these genes are important for the regulation, metabolism, and transport of various sugars; however, other genes may carry and spread virulence and antibiotic resistance determinants. In this way, monitoring these genomes is essential to the manufacture of food. In this study, we aim to provide an overview of the genomic properties of L. plantarum based on approaches of comparative genomics. Results. The finding of the current study indicates that the core genome of L. plantarum presents 1425 protein-coding genes and is mostly related to the metabolic process. The accessory genome has on average 1320 genes that encodes protein involved in processes as the formation of bacteriocins, degradation of halogen, arsenic detoxification, and nisin resistance. Most of the strains show an ancestral synteny, similar to the one described in the genomes of L. pentosus KCA1 and L. plantarum WCFS1. The lifestyle island analyses did not show a pattern of arrangement or gene content according to habitat. Conclusions. Our results suggest that there is a high rate of transfer of genetic material between the strains. We did not identify any virulence factors and antibiotic resistance genes on the genomes. Thus, the strains may be useful for the biotechnology, bioremediation, and production of bacteriocins. The potential applications are, however, restricted to particular strains.